THE LEXICON OF MAJAPAHIT CULINARY AT TROWULAN IN THE GLOBALIZATION ERA - Hendra Hendra; Rode Ayu Wahyuningputri; Aditya Nova Putra; Farah Levyta (Bahasa Indonesia, 2021)
This research aims to describe the form of lingual, naming, and the meaning of lexicon and examinesMajapahit Culinary by using a linguistic approach that has similar sounds with global tourism language.The problem studied in the process of naming the Majapahit Culinary that has the same sound asEnglish as the international language. The ethnographic method is used to investigate the languageand culture related to culinary based on the understanding of the local community. This research wasconducted in Trowulan. Data collection uses in-depth interview methods and observations of theparticipation of informants. All data is reviewed using analisis domain, taxonomy, componential andthemes, obtained from written sources including inscriptions and literature from Majapahit and from thetime before and afterwards. The sources of research data are verbal words of the informants asspeakers. Data collection was carried with participant observation techniques and interviews. Dataanalysis was carried out with four activities as collection, reduction, presentation and verification. Theresult of the Majapahit culinary analysis that has naming which can be used as the basis for thereference of the global sound are five Majapahit culinary, they are Letlet, Wok, Kwelon Dodol and Lepet.Those five Majapahit culinary will become a reference in the promotion of Majapahit culinary ininternational tourism.